A Sedentary Behaviour and Role of Exercise in Anti-Aging Medicine - I Dewa Ayu Inten Dwi-Primayanti; Wimpie I. Pangkahila (Program Studi Magister Fisiologi Keolahragaan, Fakultas Kedokteran, Universitas Udayana, 2023)
The concept of anti-aging medicine is very popular these days. Many studies discuss how to inhibit the aging process so as to prevent various degenerative diseases and improve quality of life. In the concept of anti-aging medicine, aging prevention is not only based on one aspect for example aesthetics procedure that is currently popular. In the concept of anti-aging medicine, a comprehensive approach is needed to slow down the aging process, including hormonal, skin, nutritional approaches, including a healthy lifestyle. A healthy lifestyle plays an important role in the aging process itself, including physical activity. Sedentary or inactive behavior is closely related to an increased risk of diseases associated with aging. Key word: healthy life style; sedentary behavior; aging